Cell type-specific mapping of ion distribution in Arabidopsis thaliana roots - Ricardo F. H. Giehl; Paulina Flis; Jörg Fuchs; Yiqun Gao; David E. Salt; Nicolaus von Wirén (Nature Communications, 2023)
Abstract Cell type-specific mapping of element distribution is critical to fully understand how roots partition nutrients and toxic elements with aboveground parts. In this study, we developed a method that combines fluorescence-activated cell sorting (FACS) with inductively coupled plasma mass spectrometry (ICP-MS) to assess the ionome of different cell populations within Arabidopsis thaliana roots. The method reveals that most elements exhibit a radial concentration gradient increasing from the rhizodermis to inner cell layers, and detected previously unknown ionomic changes resulting from perturbed xylem loading processes. With this approach, we also identify a strong accumulation of manganese in trichoblasts of iron-deficient roots. We demonstrate that confining manganese sequestration in trichoblasts but not in endodermal cells efficiently retains manganese in roots, therefore preventing toxicity in shoots. These results indicate the existence of cell type-specific constraints for efficient metal sequestration in roots. Thus, our approach opens an avenue to investigate element compartmentation and transport pathways in plants.